2020
DOI: 10.1186/s13018-020-02057-y
|View full text |Cite
|
Sign up to set email alerts
|

Pin vs plate fixation for metacarpal fractures: a meta-analysis

Abstract: Background The differences in the clinical and functional outcomes of closed reduction and percutaneous pin fixation and open reduction with internal fixation (ORIF) using plate and screws have been systematically synthesized by one meta-analysis. With newer studies being published, an effort to update the earlier meta-analysis is necessary. Methods Comprehensive searches were done systematically through PubMed, Scopus, CENTRAL (Cochrane Central Register of Controlled Trials), and Google scholar databases. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…25 Other commonly reported postoperative complaints in our cohort, such as contractures and extensor lag, were not described in most studies captured by the meta-analysis. 24,26 In the current cohort of metacarpal fixation patients, approximately half (51.3%) of our reported complications were symptoms of stiffness. Stiffness has been associated with factors external to intraoperative technique, such as immobilization time and postoperative therapy regimen.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…25 Other commonly reported postoperative complaints in our cohort, such as contractures and extensor lag, were not described in most studies captured by the meta-analysis. 24,26 In the current cohort of metacarpal fixation patients, approximately half (51.3%) of our reported complications were symptoms of stiffness. Stiffness has been associated with factors external to intraoperative technique, such as immobilization time and postoperative therapy regimen.…”
Section: Discussionmentioning
confidence: 72%
“…Although less prevalent than with phalangeal fracture fixation, complications after metacarpal fixation are still common. 24 , 25 A recent meta-analysis of comparative studies examining pin versus plate fixation of metacarpal fractures demonstrated complications occurring in 40 out of 249 pooled subjects (16%). 24 However, unlike the current study, many of the studies described by this meta-analysis did not report minor complaints, such as stiffness, which may have contributed to the discrepancy in overall complication rates.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this retrospective study was to demonstrate the performance and safety of the Stryker Hand Plating System. This study differs from many publications that either compare different osteosynthesis procedures or focus on finger function [ 8 ], [ 9 ]. All patients of our hospital which underwent reconstruction of finger fractures with plate and with complete documentation were included.…”
Section: Discussionmentioning
confidence: 88%
“…The surgical indications for the fifth metacarpal neck fracture have always been controversial [ 11 13 ]. For the fifth metacarpal neck fractures with angulation more than 30°, most surgeons agree that surgical treatment is more effective than conservative treatment [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%